Quality evaluation of primary health care an urban area of southern Brazil - Halal, Iná S.; Sparrenberger, Felipe; Bertoni, Anete M.; Ciacomet, Carla; Seibel, Carlos E.; Lahude, Flávia M.; Magalhães, Gilson A.; Barreto, Lirio; Lira, Rita C.A. (Revista de Saúde Pública, 1994)
A 10% sample of patients who attended two Primary Health Care Units (PHCU) in Pelotas, RS (Brazil) was studied cross-sectinonally for the purpose of measuring qualitatively the attention being offered to the population. According to domiciliar interviews, 15 days after their appointments, a solution (cure or improvement) was achieved in 87.9% of the patients. Patients or parents satisfaction (in the case of pediatric patients) was observed in nearly 90% of the sample. Patient satisfaction and solution were statistically associated (p=0.04). Association between the solution and the availability of medicines in the PHCU was observed. Patients who had received the whole or a part of their treatment had 33% greater probability of solving their problem. Professional satisfaction was linearly associated with both perception of a better professional-patient relationship (PR=3.48; CI95%2.17-5.59) and the expectation of a better patient prognosis (PR=1.99; CI95% 1.36-2.91).